Optical fiber telecommunications IV. - Li, Tingye; Kaminow, Ivan P., 1930-
Volume B is devoted to light wave systems and system impairments and compensation. Some of the topics include growth of the Internet, network architecture, undersea systems, high speed TDM transmission, cable TV systems, access networks, simulation tools, nonlinear effects, polarization mode dispersion, bandwidth formats, and more. This book is an excellent companion to Optical Fiber Telecommunications IVA: Components (March 2002, ISBN: 0-12-395172-0). Fourth in a respected and comprehensive series- Authoritative authors from a range of organizations- Suit.